2019
DOI: 10.1097/md.0000000000015307
|View full text |Cite
|
Sign up to set email alerts
|

Plasma exchange improves outcome of sepsis-associated liver failure

Abstract: Rationale: Sepsis-associated liver failure is characterized by increased bilirubin levels and coagulation disorders, which has a significant impact on mortality due to the insufficient understanding of its complicated pathogenesis pathophysiology and a lack of standardized treatment. Patient concerns: A 56-year-old woman presented signs of sepsis on the 2nd day after undergoing ureteroscopy for left ureter and laparoscopy for lysis of adhesions around left ureter due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Since sepsis‐associated liver failure is linked with poor survival (Yan et al , 2014; Ye et al , 2019), targeted delivery of AS605240 through T‐LipoAS improved liver function and overall outcome (Fig 5). The chosen sepsis model aimed to mimic a clinical situation.…”
Section: Resultsmentioning
confidence: 99%
“…Since sepsis‐associated liver failure is linked with poor survival (Yan et al , 2014; Ye et al , 2019), targeted delivery of AS605240 through T‐LipoAS improved liver function and overall outcome (Fig 5). The chosen sepsis model aimed to mimic a clinical situation.…”
Section: Resultsmentioning
confidence: 99%
“…Since sepsis-associated liver failure is linked with poor survival, 25,26 targeted delivery of AS605240 through T-LipoAS improved not only liver function but also overall outcome ( Figure 5 ). The chosen sepsis model aimed to mimic a clinical situation.…”
Section: Resultsmentioning
confidence: 99%
“…Larsen et al showed in their study of adults that plasmapheresis was effective in the treatment of patients with acute liver failure without the need for liver transplantation [ 15 ]. In another study, it was reported that TPE can be applied in cases where there is no response to other treatments in hepatic failure due to sepsis [ 16 ]. In our study, two of the 5 patients who underwent TPE due to liver failure were discharged, two were transferred to the transplantation center, and one patient died.…”
Section: Discussionmentioning
confidence: 99%